Synthesis, characterization and pharmacological properties of some 4-arylhydrazono-2-pyrazoline-5-one derivatives obtained from heterocyclic amines - (:unkn) unknown (ELSEVIER FRANCE-EDITIONS SCIENTIFIQUES MEDICALES ELSEVIER, 2000)
The synthesis of a new series of 4-arylhydrazono-2-pyrazoline-5-ones 7-24 and 22a is described. Structures of the synthesized compounds were confirmed using UV, IR, H-1-NMR, C-13-NMR and EI-mass spectral data. These compounds were tested in vitro against one Gram-positive and two Gram-negative bacterial strains, two mycobacterial strains and a fungus, Candida albicans. Compound 22 was found to be more active against Staphylococcus aureus than the other compounds at a concentration of 15.6 mu g/mL. Some related compounds were evaluated for anticonvulsant activity. Compound 11 showed 40% protection against pentylenetetrazole-induced seizures in albino Swiss mice. In vitro antituberculosis activity of 4-arylhydrazono-2-pyrazoline-5-ones 7-12, 14-24, 22a and coupling products 6a-f were tested on Mycobacterium tuberculosis H37Rv. Of these compounds, only 24, which exhibited > 90% inhibition in the primary screen at 12.5 mu g/mL against this strain was re-examined for determination of its actual MIC. However, level II assay revealed that the MIC value was not less than 12.5 mu g/mL. The same compound was also tested against Mycobacterium avium, which was observed not to be susceptible to 24. (C) 2000 Editions scientifiques et medicales Elsevier SAS.
Keywords: 4-arylhydrazono-2-pyrazoline-5-one; BACTEC 460 radiometric system; antimicrobial activity; anticonvulsant activity; reductive cleavage; AZOPYRAZOLE DERIVATIVES; ANTICONVULSANT AGENTS; ANTIBACTERIAL